DESAIN DATABASE PENGELOLAAN ADMINISTRASI PADA INTERNSHIP AND RESEARCH APPLICATION SYSTEM BAGI PARA PELAJAR DI KEMENTERIAN KOMUNIKASI DAN INFORMATIKA (KOMINFO) - Shabrina (2021)
The management of internships and research at the Ministry of Communication and Informatics (Kominfo) is still done manually and the data received or issued is still in the form of archives so that the management of internships and research for students and students is still not optimal. With the database design and apprenticeship and research management systems for students and students, it can help manage data systematically, effectively, and efficiently. The purpose of this study was to design a database which is a support in making an apprenticeship and research management system for students and students. Utilization ofdesign database in the field of internship and research, especially for managing incoming and outgoing documents systematically and managing submissions, admissions, and scheduling quickly and easily. By using themethod Data Base Life Cycle which has several stages ofdesign database detailed, it is hoped that it can help in solving problems in managing internships and research at the Ministry of Communication and Informatics (Kominfo). The results of this research are in the form of adesign databaseinternship application system for apprenticeship management and research at the Ministry of Communication and Information Technology (Kominfo). Of course, with the implementation of this research, it is hoped that it can produce a useful outcome for the Ministry of Communication and Informatics (Kominfo) as well as students and students.